Synthesis of amphiphilic copolymers based on dendritic polyethylene grafted by polyhydroxyethylmethacrylate and polyhydroxypropylmethacrylate and their use for construction of nanoparticles. (June 2019) - Nunvářová, Kateřina; Charvátová, Barbora; Šlouf, Miroslav; Hermanová, Soňa; Merna, Jan
Graphical abstract: Highlights: Amphiphilic copolymers with dendritic PE core and polyHEMA grafts prepared. dPE-graft-PHEMA form 60–180 nm nanoparticles stable in water. Self-assembly behavior is influenced by molar mass of copolymers. Nanoparticles encapsulate hydrophobic Nile Red dye with up to 25% efficiency. Abstract: By grafting from approach amphiphilic grafted copolymers with a hydrophobic core based on dendritic polyethylene and hydrophilic grafts of polyhydroxyethylmethacrylate (PHEMA) and polyhydroxypropylmethacrylate (PHPMA) were synthesized by tandem chain walking copolymerization and ATRP. Copolymers with molar mass 160–1400 kg/mol and ∼50–90% of hydrophilic grafts were obtained. Core-shell nanoparticles with very narrow size distribution were prepared from the copolymers by solvent displacement method. Particles diameter was efficiently regulated by molar mass of the copolymers in the range of 60–180 nm. We demonstrated that these nanoparticles can act as nanocontainers for hydrophobic Nile red dye, achieving up to 25% encapsulation efficiency. Dendritic polyethylene (dPE) nanoparticles with biocompatible polar PHEMA and PHPMA shell can find application in nanocatalysis and cargo delivery.